Surface Defect Suppression for High Color Purity Light‐Emitting Diode of Free‐Standing Single‐Crystal Perovskite Film - Li, Lutao; Hu, Yun; Chen, Yuan; Wang, Chen; Zhao, Guoxiang; Du, Xinyu; Wang, Chaoqiang; Xiao, Lingbo; Lu, Zheng; Wang, Jiong; Wang, Dan; Jie, Jiansheng; et al. (Advanced functional materials, 2023)
High color purity is one of the important features for single‐crystal metal halide perovskite light‐emitting diode (LED). Despite single‐crystal perovskite showing low bulk defect concentration, single‐crystal perovskite LEDs do not exhibit high color purity advantage due to the absence of effective surface defect passivation. Herein, one fully wrapped structure is proposed to passivate the surface of the free‐standing CsPbBr3 single‐crystal films. The surface of CsPbBr3 single‐crystal films is wrapped by ultra‐thin polymethyl methacrylate, precisely controlling the thickness. The single‐crystal perovskite film device can achieve high color purity with a full width at half maximum (FWHM) of 15.8 nm) and a large luminescent area of 2.25 mm2. It is observed that surface passivation is due to interaction of CO bond in polymer chains with the Lewis acid PbBr2. The passivated perovskite single‐crystal films significantly improve carrier lifetime and suppress surface defects. It is noteworthy that the passivated free‐standing single‐crystal perovskite films are feasible to build up a vertical LED device structure, avoiding the edge glowing and short‐circuiting of the LED device. This study demonstrates the large luminescent area of the high‐quality millimetre‐scale free‐standing single‐crystal films for wide color gamut display and vertical optoelectronic devices. A fully wrapped structure is proposed to passivate the surface of the free‐standing CsPbBr3 single‐crystal films in light‐emitting diode device, which can achieve high color purity (FWHM = 15.8 nm) and realize a large luminescent area (>2 mm2). This study represents remarkable advancement in single‐crystal perovskite materials and feasibility of free‐standing film‐based device.